HYPOCENTER RELOCATION AND FOCAL MECHANISM OF DISTAL VOLCANO-TECTONIC EARTHQUAKE SWARM NEAR AGUNG VOLCANO, BALI - AL FATIH - NIM: 12314020 , GHILMAN
After has been dormant for 54 years, Mount Agung, Bali, has showed significant increase of seismic activity since September 2017 culminating with a great explosive eruption two months later. This increase in seismic activity was dominated by distal volcano-tectonic earthquake swarm located at 3-10 km north west from the eventual eruption vent, right between Mt. Batur Caldera and Mt. Agung. This similar events has preceded many long dormant explosive eruptions in the world and has proven as earliest warning before the eruption begins. This study has relocated hypocenter and determined moment tensor solution for the swarm. Arrival time was corrected with waveform cross correlation as a correction for parameter used in double difference relocation. The relocation results show better residual and hypocenter distribution which consistent with the effect of magma plumbing system modeled from previous studies. Moment tensor results from two biggest events show complex interaction between tectonic and volcanic effect in this swarm. Its tectonic feature were consistency of faulting parameter with dominant regional structure. Sign of volcanic influence is dominant non double-couple component in the solutions. This results indicated that intruded magma may have heated fluid in the vicinity of pre-existing fault, increased its pore pressure, and together with tectonic stresses triggered an earthquake swarm that failed in context of regional structures.